Fatigue Fracture Strength of Implant-Supported Full Contour Zirconia and Metal Ceramic Fixed Partial Dentures - Vafaee, Fariborz (J Dent (Tehran), 2017)
OBJECTIVES: Zirconia restorations have been suggested as a more durable and more appealing alternative to metal restorations. However, their mechanical properties may be negatively affected by fatigue due to superficial stresses or low temperature degradation. This study aimed to assess the fatigue fracture strength of three-unit implant-supported full contour zirconia and pre-sintered cobalt-chromium (Co-Cr) alloy posterior fixed partial dentures (FPDs). MATERIALS AND METHODS: In this in-vitro experimental study, 28 posterior three-unit implant-supported FPDs were fabricated of full contour zirconia and pre-sintered Co-Cr alloy, and were cemented on implant abutments. To simulate the oral environment, FPDs were subjected to 10,000 thermal cycles between 5–55°C for 30 seconds, and were then transferred to a chewing simulator (100,000 cycles, 50 N, 0.5 Hz). Afterwards, fatigue fracture strength was measured using a universal testing machine. Data were analyzed by Mann-Whitney U test. RESULTS: The mean and standard deviation of fracture strength were 2108.6±440.1 N in full contour zirconia, and 3499.9±1106.5 N in pre-sintered Co-Cr alloy. According to Mann-Whitney U test, the difference in this respect was statistically significant between the two groups (P=0.007). CONCLUSIONS: Since the fracture strength values obtained in the two groups were significantly higher than the maximum mean masticatory load in the oral environment, both materials can be used for fabrication of posterior three-unit FPDs, depending on the esthetic demands of patients.